Assessing the impact of shared decision making processes on influenza vaccination rates in adult patients in outpatient care: A systematic review and meta-analysis. Issue 2 (8th January 2021) - Sanftenberg, Linda; Kuehne, Flora; Anraad, Charlotte; Jung-Sievers, Caroline; Dreischulte, Tobias; Gensichen, Jochen
Highlights: Shared decision making increases influenza vaccination rates in adult patients. Interventions focused only on patient activation, might not be sufficient. A multidisciplinary approach of health care providers showed effectiveness. Abstract: Background: Shared decision making (SDM) is a promising approach, to bridge major barriers concerning vaccination by patient education and personal interaction of health care provider (HCP) and patient. SDM affects patient adherence, enhances patient knowledge, decreases decisional conflict and improves trust in the physician in most areas of health care. The shared decision making process (SDM process) is characterised by three key components: patient activation, bi-directional exchange of information and bi-directional deliberation of options. Objectives: To assess the impact of SDM processes on influenza vaccination rates in outpatient care patients. Methods: A systematic literature search in MEDLINE, CENTRAL, EMBASE, PsycINFO and ERIC was conducted (2020–02-05). Randomized controlled trials (RCTs) and cluster RCTs, that aimed to improve influenza vaccination rates in adult patients in outpatient care were included. We examined effects of SDM processes on influenza vaccination rates by meta -analysis, and considered the extent of SDM processes in the analysed interventions and possible effect modifiers in subgroup analyses. Results: We included 21 studies, with interventions including face-to-face sessions, telephone outreach, home visits, Health Care Practitioner (HCP) trainings and supporting educational material. In 12 studies, interventions included all elements of a SDM process. A meta -analysis of 15 studies showed a positive effect on vaccination rates (OR of 1.96 (95% CI: 1.31 to 2.95)). Findings further suggest that interventions are effective across different patients groups and could increase effectiveness when the interaction is facilitated by multidisciplinary teams of HCP in comparison to interventions delivered by individual HCP. Discussion: This systematic review and meta -analysis provide evidence that SDM processes can be an effective strategy to increase influenza vaccination rates. Further research with more detailed descriptions of SDM implementation modalities is necessary to better understand which components of SDM are most effective. Trial Registration: PROSPERO: CRD42020175555